L’antiféminisme « ordinaire » - Descarries, Francine (Recherches féministes, 2005)
L‘antiféminisme se nourrit du ressentiment explicite à l’égard des femmes et de leurs avancées vers l’égalité. Pilier du sexisme qui perdure sur le plan des mentalités, des structures et des institutions, l’antiféminisme ordinaire s’appuie sur une représentation essentialisée des femmes pour soutirer leur conformité aux diktats de l’ordre patriarcal et récuser la conception égalitaire des rapports entre les femmes et les hommes. Le présent texte cherche à illustrer comment, encore aujourd’hui, les grands archétypes du féminin, qui constituent le « prêt à penser » de la tradition patriarcale, sont au coeur des représentations sociales, préjugés et stéréotypes véhiculés par l’antiféminisme et tissent la trame de fond de sa contre-offensive actuelle.
http://www.erudit.org/fr/revues/rf/2005-v18-n2-rf1048/012421ar/
Keywords: antiféminisme; approches et analyses; cours; discipline; fem1000; histoire; patriarcat; premier cycle; ressource en ligne; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; études culturelles

Sains et saufs : petit manuel de lutte contre l'homophobie à l'usage des jeunes - Dorais, Michel; Verdier, Éric (VLB, 2005)
Section: 166, [10] pages ; 19 cm
Keywords: EDI; LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétéronormativité; identités LGBTQIA2+; intervention sociale; justice sociale; premier cycle; psy4910; pédagogie; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social; violences

Black sexual politics: African Americans, gender, and the new racism - Hill Collins, Patricia (Routledge, 2005)
To a large extent, scholarship on black politics often focuses primarily on institutions, rule of law, processes, political actors, and citizens but with very little attention to issues of gender and sexuality. In contrast, the principal aim of this book is to explore what the author sees as the inextricable links between racism and gender. The basic thesis of this well-written, important, and provocative book is that the fight against racism, especially the “new racism,” can never be won without first challenging sexism, which simultaneously oppresses African-American men and women.
Section: ix, 374 p. ; 23 cm
Keywords: afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminismes noirs; intersectionnalité; premier cycle; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; théorie critique de la race; violences; états-unis

Attitudes Toward Victims of Rape: Effects of Gender, Race, Religion, and Social Class - Nagel, Barbara; Matsuo, Hisako; McIntyre, Kevin P.; Morrison, Nancy (Journal of Interpersonal Violence, 2005)
Although previous literature focusing on perceptions of victims of rape has examined how gender, race, and culture influence the attitudes one holds toward victims, these studies have yielded mixed results. This study compared perceptions of victims of rape across a wide range of ages, educational backgrounds, religions, and income levels, while focusing on gender and racial differences. Results indicate (N = 220) that victims of rape are generally viewed more sympathetically by females than by males and by Whites than by African Americans. However, the effect of race disappears when socioeconomic variables are controlled, suggesting a more complex relationship. Also, a hierarchical regression indicates that age, sex, education, and income are significant predictors of attitudes toward victims. This study builds on existing research that examines such attitudes from a cultural perspective and extends this literature by examining the interactive effects of several demographic variables within a community sample.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; viol; violences; états-unis

C'était du spectacle! L'histoire des artistes transsexuelles à Montréal, 1955-1985 - Namaste, Viviane K. (McGill-Queen's University Press, 2005)
Le quartier chaud de Montréal a fait couler beaucoup d'encre, mais sa culture de cabaret n'a jamais été examinée dans la perspective des artistes transsexuelles et travesties qui l'ont rendu si populaire. Par le biais des récits provenant des danseuses elles-mêmes, Viviane Namaste peint un portrait honnête de quatorze transsexuelles - danseuses, chanteuses, magiciennes ou effeuilleuses - et jette un regard dans les coulisses du monde dans lequel vivent et travaillent ces hommes devenus femmes. Les années soixante et soixante-dix ont été des décennies de changement social au Québec. C'était du spectacle! raconte l'histoire de la première génération de transsexuelles ayant subi une chirurgie d'inversion de sexe. Namaste examine les conditions de travail dans les cabarets, la prostitution, les abus de pouvoir des policiers à l'égard des transsexuelles, le rôle du crime organisé dans la vie nocturne de la ville et l'accès aux soins de la santé. C'était du spectacle! offre un rare survol de la culture urbaine de Montréal, présenté dans ses propres mots par l'une de ses plus importantes communautés artistiques.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; LGBTQIA2+; amériques; artistes trans*; discipline; environnement; histoire; identités LGBTQIA2+; montréal; personnes trans*; périodes historiques; régions géographiques; santé; sciences humaines; thématiques; travail; travail du sexe; violences; violences policières

Domestic violence at the intersections of race, class, and gender: challenges and contributions to understanding violence against marginalized women in diverse communities - Sokoloff, Natalie J; Dupont, Ida (Violence against women, 2005)
This article provides a comprehensive review of the emerging domestic violence literature using a race, class, gender, sexual orientation intersectional analysis and structural framework fostered by women of color and their allies to understand the experiences and contexts of domestic violence for marginalized women in U.S. society. The first half of the article lays out a series of challenges that an intersectional analysis grounded in a structural framework provides for understanding the role of culture in domestic violence. The second half of the article points to major contributions of such an approach to feminist methods and practices in working with battered women on the margins of society.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; care; corps; cours; criminologie; discipline; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; violences; états-unis

Make Room for Daddy: Anxious Masculinity and Emergent Homophobias in Neopatriarchal Politics - Stein, Arlene (Gender and Society, 2005)
What are the sources of continuing antipathy toward homosexuality, and what might they tell us about changing forms of American masculinity? This article documents some emergent homophobias circulating among conservative activists in relation to campaigns against gay rights in the early 1990s and against gay marriage in 2004. As feminist critiques of traditional masculinity make their way into conservative rhetoric and as men struggle to define a role that maintains male authority without sounding overly authoritarian, new forms of homophobia have emerged that are compatible with conservatives' quest to be seen as compassionate protectors of the family.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; homophobie; hétérosexisme; masculinité; militance; patriarcat; premier cycle; périodes; périodes historiques; régions géographiques; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; états-unis